The miracle of the dead lad in the Sofia Second Chronicle - Elvina Vitalievna Kapustina, Alexander Leonidovich Novoselov, (Opción, 2019)
The article interprets the Miracle of the Dead Lad in the Sofia Second Chronicle via hermeneutic and semiotic analysis, as well as a historical and anthropological approach. In result, this same miracle, probably based on the text of Rodion Kozhuch, will later be added by Pakhomiy Logofet (Serb) to his version of the Life of Varlaam Khutynsky. The conclusion is made about the complex structure of the text of the Miracle of the Dead Lad in the Sofia Second Chronicle, which contains both ideas about illness, healing, holiness, and the chronicler’s assessment of ecclesiastical, political and eschatological problems.